NBS1 plays a synergistic role with telomerase in the maintenance of telomeres in Arabidopsis thaliana - Najdekrova, Lucie; Siroky, Jiri (BMC plant biology, 2012)
BACKGROUND: Telomeres, as elaborate nucleo-protein complexes, ensure chromosomal stability. When impaired, the ends of linear chromosomes can be recognised by cellular repair mechanisms as double-strand DNA breaks and can be healed by non-homologous-end-joining activities to produce dicentric chromosomes. During cell divisions, particularly during anaphase, dicentrics can break, thus producing naked chromosome tips susceptible to additional unwanted chromosome fusion. Many telomere-building protein complexes are associated with telomeres to ensure their proper capping function. It has been found however, that a number of repair complexes also contribute to telomere stability. RESULTS: We used Arabidopsis thaliana to study the possible functions of the DNA repair subunit, NBS1, in telomere homeostasis using knockout nbs1 mutants. The results showed that although NBS1-deficient plants were viable, lacked any sign of developmental aberration and produced fertile seeds through many generations upon self-fertilisation, plants also missing the functional telomerase (double mutants), rapidly, within three generations, displayed severe developmental defects. Cytogenetic inspection of cycling somatic cells revealed a very early onset of massive genome instability. Molecular methods used for examining the length of telomeres in double homozygous mutants detected much faster telomere shortening than in plants deficient in telomerase gene alone. CONCLUSIONS: Our findings suggest that NBS1 acts in concert with telomerase and plays a profound role in plant telomere renewal.
Keywords: proteiny huseníčku; semena rostlinná; chromozomální nestabilita; Chromosomal Instability; telomerasa; MRE11 Homologue Protein; Arabidopsis; hybridizace in situ fluorescenční; klíčení; Arabidopsis Proteins; Germination; mapování interakce mezi proteiny; jaderné proteiny; Meiosis; květy; DNA vazebné proteiny; Seeds; chromozomy rostlin; Telomere Homeostasis; Chromosomes, Plant; Protein Interaction Mapping; proteiny buněčného cyklu; DNA Repair; oprava DNA; meióza; rostlinné buňky; Telomerase; Flowers; anafáze; telomery; Anaphase; Plant Cells; Self-Fertilization; In Situ Hybridization, Fluorescence; homeostáza telomer; cytogenetické vyšetření; homologní protein MRE11; Cell Cycle Proteins; DNA-Binding Proteins; samooplození; Nuclear Proteins; Cytogenetic Analysis; Telomere